Exploring Trends and Challenges in Professional Development of Adult Educators across European Member States: Insights and Recommendations for Improvements - Ioannou, Nicoletta (Social Education Research, 2024)
This article provides an overview of professional development trends in European Member States, encompassing training and qualification requirements, as well as the supply and demand for adult teaching staff, including specialized training in andragogical studies. The study investigates actions and policies related to professional development in selected European Member States through thematic analysis of a supportive document for National Coordinators of Adult Learning, who participated in an online Peer Learning Activity (PLA) in May 2021. Additionally, relevant information from Eurydice, European policy documents, scholarly articles, and research papers is incorporated. This overview sets the stage for a discussion on prevailing trends in the professional development of adult educators across European Member States and explores how these trends impact professional development. Overall, the discussion underscores the need for a more systematic and sustained approach to professional development and professionalization in the field of adult education. This includes addressing the diverse needs of adult educators and advocating for greater recognition and regulation of the profession across European countries.